2008
DOI: 10.1021/jo800788s
|View full text |Cite
|
Sign up to set email alerts
|

Benzoboroxoles as Efficient Glycopyranoside-Binding Agents in Physiological Conditions: Structure and Selectivity of Complex Formation

Abstract: In contrast to normal boronic acids, o-hydroxymethyl phenylboronic acid (benzoboroxole) has the capability of complexing glycopyranosides efficiently in neutral water. The measurement of association constants with a panel of model hexopyranosides indicates that the preferred mode of binding is through a cis-3,4-diol, such as that found in galactopyranosides, and mass spectrometric studies support a 1:1 binding stoichiometry. The complexation of glucopyranosides is weaker, and they are bound through their 4,6-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(82 citation statements)
references
References 52 publications
0
81
1
Order By: Relevance
“…Sumerlin and coworkers demonstrated that linkage of the phenylboronic acid moiety through the electronwithdrawing carboxyl rather than amino group of an amide (54) results in similarly enhanced sugar binding at neutral pH [41]. In a different approach, Kiser and coworkers incorporated more acidic boroxoles [139,140] into polymer structures [141][142][143][144]. Related block copolymers (55,56) were investigated by Kim and coworkers as building blocks of responsive vesicles for insulin release applications [36,40].…”
Section: Boronic and Borinic Acid-functionalized Polymers For Biomedimentioning
confidence: 99%
“…Sumerlin and coworkers demonstrated that linkage of the phenylboronic acid moiety through the electronwithdrawing carboxyl rather than amino group of an amide (54) results in similarly enhanced sugar binding at neutral pH [41]. In a different approach, Kiser and coworkers incorporated more acidic boroxoles [139,140] into polymer structures [141][142][143][144]. Related block copolymers (55,56) were investigated by Kim and coworkers as building blocks of responsive vesicles for insulin release applications [36,40].…”
Section: Boronic and Borinic Acid-functionalized Polymers For Biomedimentioning
confidence: 99%
“…As a prelude, in 2006, the Hall lab first reported ortho-hydroxymethyl phenylboronic acid (5, Figure 1), which has a weak but encouraging binding with a model of hexopyranosides (methyl α-D-glucopyranoside). 23,24 This is especially important, since carbohydrates found in glycoproteins, glycolipids, and lipopolysaccharides are almost always six-membered ring sugars and linear diols, while most boronic acids normally show a preference for furanose sugars in binding. Compound 5 binds methyl α-D-glucopyranoside with a K a of 22 M −1 in neutral aqueous media by complexing hexopyranosides primarily using their 4,6-diol.…”
Section: Interactions Between the Boronic Acid Unit And Nucleophiles/mentioning
confidence: 99%
“…This was followed by a decade of very active work in the design and synthesis of sensors for monosaccharides and oligosaccharides. Efforts in recent years have moved to a more biological direction, with applications in glycan analysis [29,[53][54][55][56][57], recognitions of cell-surface carbohydrate biomarkers [5,58], and glycoproteins [57], as well as array analyses [59][60][61], which is the subject of Chapter 17. For biological applications, these boronic-acid-based sensors and receptors function in a manner similar to lectins (carbohydrate-binding proteins).…”
Section: Boronic-acid-based Chemosensorsmentioning
confidence: 99%
“…Several recent reviews and research papers comprehensively summarize the use of boronic acids in sensor designs for carbohydrates [9,[14][15][16]66], fluoride [47][48][49][50][51], and cyanides [45,46], and have in-depth discussions of factors [15,19,67] that should be considered in designing such sensors. In addition, there have also been quite a few reviews [8,15,66] and research papers [54,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] on boronic acids that change their fluorescent properties upon binding to a nucleophilic analyte or pH changes. Obviously, it would not be possible to describe all these findings here; therefore, readers are referred to the above-referenced papers for details.…”
Section: Boronic-acid-based Chemosensorsmentioning
confidence: 99%
See 1 more Smart Citation